The policy on social inclusion, valuation and User Innovation and Identification of Innovative Users: An Exploratory Study in Colombia (2016)
Introduction: In Latin American countries, user innovation studies are emerging. In Colombia, for instead, we have not found evidence of formal research on user innovation. To fill this gap, this exploratory study aims to measure the percentage of user innovation in the analyzed sample and determine the characteristics of these innovative users. Methodology: This is an exploratory, cross-sectional, descriptive research. The methodology adopted by previous studies conducted in Japan, the United Kingdom and the United States was applied. A measuring instrument was applied to identify innovative users on a sample of 433 individuals in Bogotá, Colombia. Results: It was found that there are user innovation activities at the consumer level; the percentage of user innovation in the analyzed sample is 4.8% and the tendency to innovate was more pronounced among young adults under 30 who completed their high school and are attending college. Conclusions: The results of this exploratory study are an important starting point for a better understanding of user innovation activities in emerging or developing countries in Latin America.